Investigating Drug Interactions And Antibacterial Activity Of Vitamin C On Pathogenic Factors Of Escherichia Coli Clinical Isolates - Osamah A Tuqi; Aya Aziz Hussein; Tabark abdukarim Hussein; REYADH R AL-RASHIDI; Mustafa Khudair Abbas (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Today, the phenomenon of multi-drug resistance has become a major cause of concern, and insufficient achievements have been made in the development of new antibiotics for the treatment of bacterial infections. Therefore, there is an unmet need for new auxiliary search. Vitamin C is one such promising supplement. The current study was conducted with the aim of explaining the antibacterial interaction effect of vitamin C in different concentrations (5-20 mg/ml) and drugs effective on Escherichia coli bacteria. In order to collect clinical samples during the months of September to November 2022, clinical samples were collected from 100 patients suspected of urinary tract infection who referred to medical centers. For identification, biochemical tests and gram staining and culture in IMViC and EMB environments were used to see metallic green polish. Then antimicrobial sensitivity test And the effect of antibiotic on biofilm formation, the effect of antibiotic and ascorbic acid on biofilm formation, biofilm inhibition rate was done for the single and combined effects of both antimicrobial substances. Finally, in order to investigate and identify the virulence gene of the isolated strains, DNA extraction was performed by PCR method. 45 samples of urinary infection culture were identified from the total of 100 samples collected, in 45 (45%) of them colonies with metallic polish were observed. 45% were men and 55% were women, and of these, a total of 45 positive E. coli cases were found in women and 17 positive cases were seen in men. Less than one year, teenagers, young and old were divided. 2 cases (2%) were in the age group of less than one year, 3 cases (3%) were teenagers, 63 cases (63%) were young and 32 cases (32%) were in the age group of middle-aged people. In a situation where the ability to form biofilm under vitamin C (ascorbic acid) treatment was not very effective and did not differ much from normal conditions, antibiotic treatment (under MBC gentamicin treatment) was somewhat successful in inhibiting biofilm formation, finally with the combination of antibiotic and Ascorbic acid was completely isolated in many resistant strains, the inability to form biofilm was evident, and this indicated the synergistic effects in the investigated composition. As the results showed, the ability to produce biofilm in the samples that had the target genes in this study was not much different from the other samples. Considering the increasing resistance to some antibiotics and wide changes in the effective spectrum of drugs and preventing the increase of drug-resistant cases, the necessity of conducting drug sensitivity tests seems very necessary. The high prevalence of E. coli antibiotic resistance and the high percentage of resistance genes in patients suffering from infections caused by this bacterium can indicate the excessive use of antibiotics. Finally, the prevalence of antibiotic resistance is a useful marker for investigating resistance genes and can be useful in ecological investigations. Also, with clear inhibitory effects, the selected antibiotic in this study along with ascorbic acid, this vitamin can be used as a supplement in some infections caused by E. coli bacteria.